Goodnight moon - Brown, Margaret Wise, 1910-1952; Hurd, Clement, 1908- ([New York] : HarperCollins, 1982)
Goodnight to each of the objects in the great green room: goodnight chairs, goodnight comb, goodnight air.
Accelerated Reader
Keywords: Picture books; Bedtime -- Fiction